2011
DOI: 10.5056/jnm.2011.17.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Cholecystokinin on Colonic Motility in Isolated, Vascularly Perfused Rat Colon

Abstract: Background/AimsIt is generally believed that cholecystokinin (CCK) stimulates colonic motility, although there are controversial reports. It has also been suggested that postprandial peptide YY (PYY) release is CCK-dependent. Using a totally isolated, vascularly perfused rat colon, we investigated: (1) the roles of CCK and PYY on colonic motility, (2) to determine if CCK modulates PYY release from the colon to influence the motility and (3) to clarify whether the action of CCK and PYY on colonic motility is me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Endocrine routes for distal gut stimulation, including a proximal-distal hormonal loop, have repeatedly gained interest as this would contribute to an explanation of the early postprandial rise in plasma GLP-1 (43,61). Thus, in our hands glucosedependent insulinotropic polypetide (GIP, 1 nM), but not cholecystokinin (CCK, 1 nM), is able to induce GLP-1 and PYY secretion from the isolated perfused rat colon (unpublished data) in agreement with a previous study (48), but in contrast to others (31,49). However, the physiological relevance of high concentrations of duodenal hormones is questionable (24), while the neuropeptide vasoactive intestinal peptide (VIP, 10 nM), stimulating cAMP accumulation in enterocytes, also seems to be without effect on endocrine secretion from the perfused rat colon (unpublished data).…”
Section: Thereby Investigation Of the Integrated Communication Betwesupporting
confidence: 93%
“…Endocrine routes for distal gut stimulation, including a proximal-distal hormonal loop, have repeatedly gained interest as this would contribute to an explanation of the early postprandial rise in plasma GLP-1 (43,61). Thus, in our hands glucosedependent insulinotropic polypetide (GIP, 1 nM), but not cholecystokinin (CCK, 1 nM), is able to induce GLP-1 and PYY secretion from the isolated perfused rat colon (unpublished data) in agreement with a previous study (48), but in contrast to others (31,49). However, the physiological relevance of high concentrations of duodenal hormones is questionable (24), while the neuropeptide vasoactive intestinal peptide (VIP, 10 nM), stimulating cAMP accumulation in enterocytes, also seems to be without effect on endocrine secretion from the perfused rat colon (unpublished data).…”
Section: Thereby Investigation Of the Integrated Communication Betwesupporting
confidence: 93%
“…Previous studies have shown that intravenous injection of exogenous CCK increased pain perception and induced rapid colon transit in IBS patients. 18,19 Others reported that intra-arterial injection of exogenous CCK caused an increase of rat colon motility, 25 and administration of exogenous CCK induced contractile responses in isolated colonic smooth muscle cells from normal and highly inflamed human colons. 26 Therefore, although CCK receptor levels were not altered, the increased colonic CCK production may induce enhance pain perception in mouse colorectum.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of PYY are low in the fasted state and both the 3 -36 and 1-36 forms increase rapidly upon nutrient ingestion (14) . While it is well known that PYY is released in response to nutrient intake, it is also released by gastric acid, cholecystokinin (CCK), and infusion of bile acids into the ileum or colon as shown in animal studies (26,27) . Finally, PYY secretion is affected by things other than food consumption such as intestinal peristalsis and intraluminal nutrients (28,29) .…”
Section: Functions Of Peptide Yymentioning
confidence: 99%